An Extensive Case of Merkel Cell Carcinoma due to Fright of COVID-19 - Maria Danielsen; Trine Høgsberg; Henrik Frank Lorentzen; Ann-Kathrine Rahr German Rossau (Case Reports in Dermatology, 2021)
Merkel cell carcinoma (MCC) is a subtype of nonmelanoma skin cancer (NMSC) with increasing incidence. Clinically, MCC resembles other far less-aggressive NMSCs, and the pathogenesis is still not understood completely. Rapid diagnosis and treatment are essential to improve overall survival. We present a case report of a 74-year-old female, who had noticed a rapidly growing, oozing tumor on her right flank. She was hesitant to contact the dermatology ward where she had regular checkups as she was afraid of contracting COVID-19. This was in the beginning of the COVID-19 pandemic. At presentation, she had a large exophytic MCC on her right flank and multiple metastases. The disease was at a late stage, and palliative care was the only treatment option left. With this case, we wish to report a rather uncharacteristic location and size of an MCC tumor and suggest that fear of the pandemic and the COVID-19 lockdown has impacted dramatically on attendance of symptomatic patients.